2022
DOI: 10.1093/tse/tdac012
|View full text |Cite
|
Sign up to set email alerts
|

Influence factors and calculation model of the adhesion strength of clayey soil for EPB shield tunnelling

Abstract: When earth pressure balance (EPB) shield tunnels are constructed through clayey ground, the soil adheres to the cutter, cutterhead and chamber bulkhead due to the high adhesion strength between the steel and the clay, thus clogging the shield. To investigate the influence of different factors on the adhesion strength, this study used montmorillonite, kaolin and mixtures of the two as test soils. The adhesion strength between the steel and clay is determined with a customized rotary shear apparatus. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, the shear strength of the clay-metal interface decreased with the level of sand and silt compactness. Wang et al (2022b) investigated the effects of the consistency index, normal pressure, clay plasticity, contact angle, and metal surface roughness on the shear strength of the clay-metal interface. They found that normal pressure, consistency index, and hydrophilicity of the metal surface significantly influenced the shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the shear strength of the clay-metal interface decreased with the level of sand and silt compactness. Wang et al (2022b) investigated the effects of the consistency index, normal pressure, clay plasticity, contact angle, and metal surface roughness on the shear strength of the clay-metal interface. They found that normal pressure, consistency index, and hydrophilicity of the metal surface significantly influenced the shear strength.…”
Section: Introductionmentioning
confidence: 99%